ANALISIS TINGKAT KEPUASAN PENGGUNA APLIKASI MARKETPLACE TOKOPEDIA MENGGUNAKAN ALGORITMA C4.5 - Soewardy, Kenfyo; Bororing, Grace Martha Geertruida (Jurnal Informatika dan Bisnis, 2022)
The role of information systems in the business world in Indonesia has grown and reached a fairly rapid stage of progress, due to information systems in the business world, which can provide fast, accurate, and available information studies wherever needed, for example with the development of a marketplace business in Indonesia. Marketplace competition to attract potential consumers is getting tougher, therefore every marketplace company needs to maintain their user satisfaction so that they continue to use the marketplace services. The factors used to measure the level of application user satisfaction include system quality, information quality, design display quality, security, system user satisfaction. The object of this study is Tokopedia with the level of user satisfaction of the application as the variable of this study. The method used in this study is descriptive analysis with the C4.5 Decision Tree algorithm technique. Data collection is done by distributing questionnaires to Tokopedia application users and has been filled out by 114 respondents. The quality of information has the most significant influence on the level of satisfaction of the Tokopedia application users, besides the quality of the design display also has a significant influence on the level of satisfaction of the Tokopedia application users. This study shows that the level of user satisfaction with the Tokopedia application is good. The conclusion of this study is that the level of user satisfaction of the Tokopedia application isstrongly influenced by the value ofsystem quality, information quality, design display quality,security,system and service user satisfaction of the Tokopedia application. Keywords: Statisfication Level, Application User, C4.5 Algorithm, Decision Tree